2011
DOI: 10.1080/07347332.2011.615381
|View full text |Cite
|
Sign up to set email alerts
|

Death Ideation in Cancer Patients: Contributing Factors

Abstract: Advances in cancer research and therapy have improved prognosis and the quality of life of many patients. However, previous epidemiological studies in oncologic patients

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
45
2
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 20 publications
6
45
2
2
Order By: Relevance
“…This prevalence is higher than that reported among cancer outpatients of a regional cancer center in United Kingdom (7.8%) [7], among breast cancer patients undergoing surgery in Korea (10.9%) [29], among prostate cancer survivors in the United States (12.4%) [30], and among terminal cancer outpatients in Japan (8.6%) [31]. The prevalence we found in Chinese cancer inpatients is similar to that reported in other cohorts, including the 17.7% prevalence in a population-based sample of American cancer patients [32], the 15% prevalence in Japanese patients with unresectable lung cancer in Japan [33], and the 18.1% prevalence in Chinese gynecological cancer patients [20], but lower than that reported in Portuguese cancer patients referred for psychiatric consultation (34.6%) [34] and Korean stomach cancer survivors (34.7%) [35]. The prevalence variations across these studies may be partly due to the disparities in sampling methods, heterogeneity in the samples (i.e., patients with one type of cancer only vs. various types of cancer), definitions of SI (i.e., desire for hastened death vs. thoughts of ending one's life), assessment instruments (i.e., suicidal item of a depression scale vs. Beck Scale for Suicide Ideation), and the study settings (i.e., outpatient vs. inpatient).…”
Section: Discussionsupporting
confidence: 85%
“…This prevalence is higher than that reported among cancer outpatients of a regional cancer center in United Kingdom (7.8%) [7], among breast cancer patients undergoing surgery in Korea (10.9%) [29], among prostate cancer survivors in the United States (12.4%) [30], and among terminal cancer outpatients in Japan (8.6%) [31]. The prevalence we found in Chinese cancer inpatients is similar to that reported in other cohorts, including the 17.7% prevalence in a population-based sample of American cancer patients [32], the 15% prevalence in Japanese patients with unresectable lung cancer in Japan [33], and the 18.1% prevalence in Chinese gynecological cancer patients [20], but lower than that reported in Portuguese cancer patients referred for psychiatric consultation (34.6%) [34] and Korean stomach cancer survivors (34.7%) [35]. The prevalence variations across these studies may be partly due to the disparities in sampling methods, heterogeneity in the samples (i.e., patients with one type of cancer only vs. various types of cancer), definitions of SI (i.e., desire for hastened death vs. thoughts of ending one's life), assessment instruments (i.e., suicidal item of a depression scale vs. Beck Scale for Suicide Ideation), and the study settings (i.e., outpatient vs. inpatient).…”
Section: Discussionsupporting
confidence: 85%
“…This finding is consistent with those of previous studies in patients with cancer. [4], [21] Furthermore, the magnitude of the ORs for anxiety and depression for suicidal ideation and suicide attempts were higher in FCs than in the general population. [9], [10], [22] Among FCs who experienced suicidal ideation, 11.5% had attempted suicide during the previous year (data not shown).…”
Section: Discussionmentioning
confidence: 93%
“…[3] Several previous studies of the mental health of patients with cancer have reported that the risk of suicide in this group is higher than that in the general population and that vulnerability factors for suicide, such as depression, isolation, fear of being a burden, and poor prognosis, [4][6] are common in patients with cancer. However, despite increasing interest in the psychological stress suffered by caregivers, few studies have investigated the risk of suicide in FCs of patients with cancer, who are often the primary caregivers and who are subjected to an increasing burden of responsibility.…”
Section: Introductionmentioning
confidence: 93%
“…A study found that cancer patients with depressive disorder and depressive symptoms had a higher risk of attempting suicide compared with those without depression. 38 Adults who are at immediate risk for attempting suicide require emergency care and prompt treatment for depression. In addition, adults with cancer who are depressed are less likely to be adherent to medications.…”
Section: Discussionmentioning
confidence: 99%